Evaluation on ethno-medicinal importance and conservation of medicinal plant Monochoria vaginalis: S. N. L Narathota, A. P. A. Jayasiri (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Monochoria vaginalis (Diya habarala) of family PONTEDERIACEAE is an aquatic plant native to Sri Lanka with many ethno-medicinal values. This plant is used to treat numerous diseases in traditional system of medicine and used as a vegetable in some parts of the country. At present this has been included to lower risk category of IUCN Red Data Records due to reduction from its natural habitat. This study was conducted to evaluate ethno-medicinal importance, propagation and conservation of this plant. Data gathered from literature surveys, survey studies, physical parameter analysis tests and cultivation methods were utilized in this study. Illegal wetland destruction, excessive use of non-selective weedicides, climatic changes have minimized the availability of this plant. As a result, use of correct plant for drug preparation has reduced. Therefore, proper identification of this plant is also a necessity today. Diya habarala is a main ingredient of Neelyaadi oil which is used in traditional system of medicine. Cold potency of this plant reported to be one of the main Ayurveda pharmacological properties that helps in pacifying vitiated Pitta Dosha. Drug recipes including Diya habarala mainly act on integumentary system and used to treat skin rashes, ulcers, wounds and skin malignancies. Cultivation using Peat soil mixture showed good results and Tissue culture techniques can be used in conservation of this plant in future.